Wound‐associated macrophages control collagen 1α2 transcription during the early stages of skin wound healing. Issue 2 (2nd January 2013) - Rodero, Mathieu P.; Legrand, Julien M. D.; Bou‐Gharios, George; Khosrotehrani, Kiarash
Abstract Wound‐associated fibrosis is important to provide tensile strength upon wound healing but at the same time is detrimental to proper tissue regeneration. To date, there is no clear evidence of the role of macrophages and their subpopulations in the control of the kinetics of collagen production during wound healing. To evaluate in vivo the contribution of macrophages in collagen transcription, we depleted macrophages after wounding luciferase reporter mice of the collagen 1 alpha 2 (Col 1α2) promoter activity. Our data reveal that Col 1α2 starts to be transcribed at D2 after wounding, reaching a plateau after 7 days. Sustained macrophage depletion significantly reduced collagen 1α2 transcription from D4, indicating that the control of fibrosis by macrophages occurs during the early stages of the wound healing process. In conclusion, our results demonstrate an important role of wound macrophages in the control of collagen production during wound healing.